Musical anhedonia after focal brain damage. (March 2017) - Belfi, Amy M.; Evans, Erin; Heskje, Jonah; Bruss, Joel; Tranel, Daniel
Abstract: People listen to music because it is pleasurable. However, there are individual differences in the reward value of music. At the extreme low end of this continuum, individuals who derive no pleasure from music are said to have 'musical anhedonia.' Cases of acquired musical anhedonia following focal brain damage are rare, with only a handful having been reported in the scientific literature. Here, we surveyed a large sample of patients with focal brain damage to identify the frequency, specificity, and neural correlates of acquired musical anhedonia. Participants completed the Musical anhedonia Questionnaire and the Barcelona Music Reward Questionnaire (Mas-Herrero et al., 2013) to assess changes in musical enjoyment and reward following brain injury. Neuroanatomical data were analyzed with a proportional MAP-3 method to create voxelwise lesion proportion difference maps. No clear or consistent neuroanatomical correlates of musical anhedonia were identified. One patient with damage to the right-hemisphere putamen and internal capsule displayed specific and severe acquired musical anhedonia. These findings indicate that acquired musical anhedonia is very uncommon, a result which is consistent with the fact that only a small number of such cases have been reported in the literature. This rarity could have positive implications for the therapeutic potentialities of music in patients with severe neurological disorders. Highlights: Patients with focal brain damage completed musical anhedonia questionnaires. Acquired musical anhedonia was quite rare. Only one patient exhibited signs of anhedonia on all scales. This may suggest the use of music in therapeutic settings.